The Influence of Psychological Factors on Teacher Performance at the Persatuan Islam 40 Sarongge Islamic Boarding School - Anisa Siti Hodijah; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research investigates the influence of psychological factors on teacher performance and job satisfaction at Pesantren Persatuan Islam 40 Sarongge. It emphasizes the critical role teachers play in education and how their effectiveness is affected by both intrinsic and extrinsic motivations. The study identifies challenges such as lack of support and rapid technological changes that hinder teachers' ability to adapt to new teaching methods. By employing a quantitative approach through surveys, the research aims to establish correlations between psychological factors and various aspects of teacher performance, including task performance, contextual performance, and counterproductive work behavior. Ultimately, it seeks to provide insights that can enhance educational practices and policies aimed at improving teacher satisfaction and effectiveness.